∫ 0 π 1 + 4 sin 2 ( 2 x ) − 4 sin ( 2 x ) d x = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
exact. The careless mistake here is assuming x 2 = x . On the basis of this wrong assumption, the answer will come out to be different, which is also given in the options.
But the correct one is x 2 = ∣ x ∣ , leading to the correct, as solved by @brian charlesworth sir.
Problem Loading...
Note Loading...
Set Loading...
The expression under the root sign is ( 2 sin ( 2 x ) − 1 ) 2 , so the integral becomes
∫ 0 π ∣ ( 2 sin ( 2 x ) − 1 ) ∣ d x .
Now sin ( 2 x ) ≤ 2 1 on the interval [ 0 , 3 π ] and sin ( 2 x ) ≥ 2 1 on the interval [ 3 π , π ] , so we need to evaluate the integral in two parts, i.e.,
∫ 0 3 π ( 1 − 2 sin ( 2 x ) ) d x + ∫ 3 π π ( 2 sin ( 2 x ) − 1 ) d x =
( x + 4 cos ( 2 x ) ) ∣ x = 0 3 π − ( x + 4 cos ( 2 x ) ) ∣ x = 3 π π =
( 3 π + 4 cos ( 6 π ) − 4 ) − ( π − 3 π − 4 cos ( 6 π ) ) = 4 3 − 4 − 3 π .